Non-Neuroleptic Antitubercular and Anticancer Therapeutics through Rational Drug Remodelling of Phenothiazines and Related Antipsychotics - Semenya, Manare Molahlegi Dorothy (Department of Chemistry, 2021)
In light of shrinking pharmaceutical drug pipelines and drug resistance, innovative drug discovery strategies are of imperative need. Drug repurposing and related strategies such as drug rescue and drug remodelling have garnered significant research interest. Various clinically approved non-antibiotics including phenothiazines hold promise as novel classes of therapeutics in other indications. However, in addition to inherent neuroleptic properties, phenothiazines and related antipsychotics elicit adverse side effects at clinically relevant doses thus precluding their extensive clinical application. Herein, it was postulated that the selectivity of phenothiazines and related drugs for nonneuroleptic indications could be enhanced through rationalized structural remodelling. Phenothiazine and related neuroleptics are known to obey a lipophilic chromophore/basic side chain paradigm. Deviation from this paradigm is expected to decrease potential for neuroleptic effects. Therefore, the remodelling strategies involved introduction of novel functionalities that are dissimilar to native phenothiazine structures. Prior to chemical synthesis, drug metabolism and pharmacokinetic related properties were predicted in silico to assess drug-likeness of the new chemical entities derived from phenothiazines and related antipsychotics. The in silico profiling also included prediction of blood/brain partition coefficients and CNS activity to determine their likelihood of exhibiting neuroleptic effects. The new chemical entities were then evaluated against drug-susceptible Mycobacterium tuberculosis-H37Rv. Furthermore, a selected series was screened for binding to dopamine and serotonin receptors to corroborate in silico CNS activity predictions. Moreover, pharmacokinetic studies were conducted with the selected series to determine in vitro microsomal stability, kinetic solubility and in vivo toxicity profiles. Another objective of this study was to evaluate the new chemical entities for their potential as anticancer agents. The key findings herein demonstrated that it is possible to abolish neuroleptic effects through rationalized structural manipulation and still retain bio-activities of interest. Several new chemical entities including N-alkylsulfonates (DS0031, DS0032, DS0034, DS0035, DS00366) and nitrobenzenesulfonamides (DS00325, DS00326, DS00329) of phenothiazines, displayed notable antitubercular (GAST/Fe MIC90 range: 9.9-125 µM; 7H9 MIC range 12.5- 25 µg/mL) and anticancer (IC50 range 4.51-12.43 µM) activities in comparison to native phenothiazine drugs. Furthermore, in vitro and in vivo preclinical evaluation revealed favourable pharmacokinetic profiles. Overall, this study presents novel subclasses of phenothiazines that hold promise for further development as non-neuroleptic agents in either tuberculosis or cancer treatment regimens.